Analisis Hukum Kedudukan Tanah Adat di Papua - Absari M. J. Welang; Yoan B. Runtunuwu; Henry N. Lumenta (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
The main objective of this study is to determine the legal strength of the status of customary land rights in Papua and how to resolve conflicts that occur in Papua. This study uses normative legal research. The results of this study indicate that customary land in Papua has legal force recognized by various regulations, but in practice there is often confiscation without a legal mechanism due to weak law enforcement and overlapping claims. Conflict resolution is recommended through non-litigation channels such as mediation and customary consultation, with litigation as a last resort. The government needs to strengthen the protection of customary rights, map customary areas, and prioritize a deliberation approach in resolving disputes by forming a special team involving customary law experts, anthropologists, and community leaders to maintain justice for indigenous peoples.